Pengaruh Aset Pajak Tangguhan Beban Pajak Tangguhan dan Kepemilikan Manajerial Terhadap Manajemen Laba: Studi empiris pada Perusahaan Manufaktur Consumer Non-Cyclical 2019-2024 - Siti Aisyah Simamora; Desy Purwasih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Earnings management remains a critical topic in financial reporting, as it can mislead stakeholders and distort the actual financial performance of a company. This study aims to analyze and test the effect of deferred tax assets, deferred tax expenses, and managerial ownership on earnings management in Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The motivation behind this research stems from the increasing concerns over the use of tax-related components and ownership structures as instruments in manipulating financial outcomes. The research employs a descriptive method with a quantitative approach, utilizing secondary data sourced from published financial statements and annual reports. The sample is selected through purposive sampling based on specific criteria, resulting in a total of 10 companies being analyzed. The analytical techniques applied include descriptive statistics, panel data regression, classical assumption tests, multiple linear regression, and hypothesis testing to ensure robust and valid results. The findings reveal that deferred tax assets do not significantly affect earnings management practices. In contrast, deferred tax expenses and managerial ownership are found to have a significant influence on earnings management. Furthermore, when tested simultaneously, deferred tax assets, deferred tax expenses, and managerial ownership collectively exhibit a significant effect on earnings management. These results imply that while not all tax-related variables influence earnings manipulation, certain components—particularly deferred tax expenses and ownership structure—play a pivotal role. This study contributes to the literature by providing empirical evidence on the relevance of tax accounting and governance mechanisms in shaping earnings quality.